If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6x = 36 Solving 9 + 6x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 6x = 36 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 36 + -9 6x = 36 + -9 Combine like terms: 36 + -9 = 27 6x = 27 Divide each side by '6'. x = 4.5 Simplifying x = 4.5
| 6+5x=456 | | 2senx(cos^2x)-senx=0 | | 2cos^2-5cosx+2=0 | | 3senx+cosx-3=o | | x+2y=123 | | 3senx+cosx-3=0 | | 6(4-x)+55=5(2+3x) | | 26x^2-130x-104=0 | | 5-3x+1=-3 | | x/10-3=7 | | 153.48=2.26w+15.68 | | logy=1.9 | | 5-3x+1=4x-3 | | 19.5=2.26w+15.86 | | 10x+2y*2y=100 | | 2timesy=3.6 | | .5+2.5y=2.6+0.4y | | x+y-62=-27 | | 10(3x+19)=70 | | 7(3s+3)=252 | | (-5/28Z^7)(7/20z^2) | | 5x^2+3xy-2y^2=2 | | 3*y*log(y)-e^-((30/e-30*y)^4)/20 | | 11x+66y=3z | | -0.2+0.4x=-6.5+2.5x | | .36(6)+.6x=.12(36+x) | | -21=5x-10 | | 5(a-2)=85 | | -(-8x)=(-66) | | 9x-8=5+20 | | 6x+6=34-4x | | x^2=20.2 |